A role for actomyosin contractility in Notch signaling - Ginger L. Hunter; Li He; Norbert Perrimon; Guillaume Charras; Edward Giniger; Buzz Baum (BMC Biology, 2019)
Abstract Background Notch-Delta signaling functions across a wide array of animal systems to break symmetry in a sheet of undifferentiated cells and generate cells with different fates, a process known as lateral inhibition. Unlike many other signaling systems, however, since both the ligand and receptor are transmembrane proteins, the activation of Notch by Delta depends strictly on cell-cell contact. Furthermore, the binding of the ligand to the receptor may not be sufficient to induce signaling, since recent work in cell culture suggests that ligand-induced Notch signaling also requires a mechanical pulling force. This tension exposes a cleavage site in Notch that, when cut, activates signaling. Although it is not known if mechanical tension contributes to signaling in vivo, others have suggested that this is how endocytosis of the receptor-ligand complex contributes to the cleavage and activation of Notch. In a similar way, since Notch-mediated lateral inhibition at a distance in the dorsal thorax of the pupal fly is mediated via actin-rich protrusions, it is possible that cytoskeletal forces generated by networks of filamentous actin and non-muscle myosin during cycles of protrusion extension and retraction also contribute to Notch signaling. Results To test this hypothesis, we carried out a detailed analysis of the role of myosin II-dependent tension in Notch signaling in the developing fly and in cell culture. Using dynamic fluorescence-based reporters of Notch, we found that myosin II is important for signaling in signal sending and receiving cells in both systems—as expected if myosin II-dependent tension across the Notch-Delta complex contributes to Notch activation. While myosin II was found to contribute most to signaling at a distance, it was also required for maximal signaling between adjacent cells that share lateral contacts and for signaling between cells in culture. Conclusions Together these results reveal a previously unappreciated role for non-muscle myosin II contractility in Notch signaling, providing further support for the idea that force contributes to the cleavage and activation of Notch in the context of ligand-dependent signaling, and a new paradigm for actomyosin-based mechanosensation.